Towards Industry 5.0: A Bibliometric Analysis of Green Finance, Digital Transformation, and ESG Research (The Lumbini Journal of Business and Economics, 2026)
Purpose: The convergence of green finance, digital transformation, and environmental, social, and governance (ESG) frameworks represents one of the most consequential developments in contemporary financial scholarship, yet its collective intellectual structure remains unmapped. This study aims presents the first comprehensive bibliometric analysis of this tripartite intersection, anchored within the emerging Industry 5.0 paradigm.Methods: Drawing on a rigorously screened corpus of 121 peer-reviewed articles retrieved from the Web of Science Core Collection, the study employs performance analysis, co-authorship network mapping, keyword co-occurrence analysis, and bibliographic coupling to reveal the field's intellectual architecture.Results: Findings demonstrate a sharp upward publication trajectory, peaking at 49 documents in 2025, with an average citation rate of 28.38 per document, signaling strong and growing scholarly impact. Seven distinct thematic clusters are identified, centered on digital finance, ESG governance, fintech adoption, and green investment. Emerging economies, particularly China and the Middle East, are driving the research frontier.Conclusion: The study concludes by proposing a strategic research agenda bridging academic mapping with actionable policy and institutional implications for the transition toward human-centric, sustainable finance.